2013
DOI: 10.1002/elan.201300196
|View full text |Cite
|
Sign up to set email alerts
|

Direct Electrochemistry and Electrocatalysis of Hemoglobin on Aligned Carbon Nanotubes Based Electrodes Modified with Au Nanoparticles and SiO2 Gel

Abstract: Here we report on the preparation and characterization of new electrodes based on aligned carbon nanotubes (ACNTs) for hemoglobin (Hb) electrochemistry and electrocatalysis. The ACNTs are obtained by a thermal chemical vapor deposition method under normal pressure. Then the electrodes are elaborated by first sputtering a thin Au film (thickness of 200 nm) onto the top of the ACNTs, and then removing the Au layer/ACNTs from the quartz substrate with the aide of hydrofluoric acid (HF) treatment. Field emission s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The ks value of 2.97 s -1 was much larger than that of 0.97 s -1 at Nafion/Hb-GR-MWCNT/CILE, [26] 1.14 s -1 at Hb/Chit-IL-Fc/Gr/GCE, [27] 1.17 s -1 at Hb immobilized on SiO2/AuNPs/ACNTs. [28] This ks value indicated that the presence of NiO nanoflower could form a suitable microenvironment that benefit the electron transfer of HRP with electrode. The effect of buffer pH on electrochemical responses of CTS/NiO-HRP/CILE was further investigated in the pH range from 3.0 to 8.0 with the results shown in Figure 5D.…”
Section: Electrochemical Investigationsmentioning
confidence: 94%
“…The ks value of 2.97 s -1 was much larger than that of 0.97 s -1 at Nafion/Hb-GR-MWCNT/CILE, [26] 1.14 s -1 at Hb/Chit-IL-Fc/Gr/GCE, [27] 1.17 s -1 at Hb immobilized on SiO2/AuNPs/ACNTs. [28] This ks value indicated that the presence of NiO nanoflower could form a suitable microenvironment that benefit the electron transfer of HRP with electrode. The effect of buffer pH on electrochemical responses of CTS/NiO-HRP/CILE was further investigated in the pH range from 3.0 to 8.0 with the results shown in Figure 5D.…”
Section: Electrochemical Investigationsmentioning
confidence: 94%
“…[44], which indicated that 3D-GR/CILE could provide a specific microenvironment that was suitable for the fast electron transfer of Hb. By the integration of cyclic voltammetric reduction peaks, the surface concentration ( *) of electroactive Hb on the electrode can be calculated from the equation: Q = nFA * [40], where Q is charge passing through the electrode with full reduction of electroactive Hb, n is the number of electron transferred, F is the Faraday's constant, A is the effective area of electrode.…”
Section: Effect Of Scan Ratementioning
confidence: 97%
“…Another biosensor to determine H 2 O 2 using VACNT, AuNPs, SiO 2 gel and hemoglobin (Hb) (SiO 2 /Hb-AuNPs/VACNT electrode), was proposed by Yang et al 100 The use of AuNPs provided better direct electrochemistry and electrocatalysis of Hb, since the voltammetric response of the Hb's heme Fe(III)/Fe(II) showed a well-defined pair of peaks and higher magnitude of peak currents. Moreover, the use of the SiO 2 gel coating was found to be important to maintain the Hb-AuNP complex immobilised on the VACNT surface.…”
Section: Enzymatic Biosensorsmentioning
confidence: 99%